2022
DOI: 10.1186/s40795-022-00651-3
|View full text |Cite
|
Sign up to set email alerts
|

Food safety practice and its associated factors among food handlers in food establishments of Mettu and Bedelle towns, Southwest Ethiopia, 2022

Abstract: Background Food safety and hygiene are currently a global health concern, especially in unindustrialized countries, as a result of increasing food-borne diseases (FBDs) and accompanying deaths. It has continued to be a critical problem for people, food companies, and food control officials in developed and developing nations. Objective The objective of the study was to assess food safety practices and associated factors among food handlers in food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
3
8
2
Order By: Relevance
“…Female food handlers made up 281 (75.5%) more of the total responders than male food handlers who made up 91 (24.5%). Tis result is in line with those of other Ethiopian research in which the majority of participants were women [18,22,23].…”
Section: Sociodemographic Characteristics Of the Respondentssupporting
confidence: 91%
“…Female food handlers made up 281 (75.5%) more of the total responders than male food handlers who made up 91 (24.5%). Tis result is in line with those of other Ethiopian research in which the majority of participants were women [18,22,23].…”
Section: Sociodemographic Characteristics Of the Respondentssupporting
confidence: 91%
“…Thus, the lack of awareness and training on the code of practice is likely to be a serious barrier in complying with food safety standards. This is because food handlers are likely to engage in poor food safety practices that would expose consumers to myriad of health conditions [9,14,17].…”
Section: Discussionmentioning
confidence: 99%
“…Foods contaminated by microbes are usually difficult to detect since these microbes are imperceptible and can cause illness [5,6]. The problem is exacerbated in countries where lack of food handling practices, inadequate food safety laws, weak regulatory systems, lack of financial resources to invest in safer equipment, and lack of food safety training are common leading to noncompliance to safe food standards [7,8,9]. Meanwhile, most foodborne diseases may be self-limiting yet, some can be very fatal leading to increased morbidity and mortality [5,10].…”
Section: Introductionmentioning
confidence: 99%
“…These diseases are the main causes of morbidity and mortality. 5,9 Studies have shown that improper food hygiene practices are one of the leading causes of diarrhea among children, 10,11 accounting for up to 70% of diarrhea cases in low-income countries. 11 Diarrhea causes substantial nutrient malnutrition, liquid losses, and decreased appetite, 12 which harms children's nutrition and can cause stunting and wasting.…”
Section: Introductionmentioning
confidence: 99%
“…Poor food handling practices are the most common source of food contamination, which leads to a variety of foodborne diseases. These diseases are the main causes of morbidity and mortality 5,9 …”
Section: Introductionmentioning
confidence: 99%